Contagion across real estate and equity markets during European sovereign debt crisis - Hui, Eddie C. M.; Chan, Ka Kwan Kevin (International Journal of Strategic Property Management, 2013)
Standard methods of testing contagion may not work well if the data set is not normally distributed. To cope with this problem, Hatemi-J and Hacker (2005) proposed a new case-resampling bootstrap method to test contagion. In this paper, we extend this method to test the parameters in the Forbes-Rigobon multivariate (FRM) test. The new method has the advantage that the bivariate model is extended to a multivariate framework which jointly models and tests all combinations of contagious linkages. We apply our method to investigate contagion across equity and real estate markets of four countries: Greece, U.K., U.S. and Hong Kong, during the European sovereign debt crisis, and compare the result with that by performing the FRM test directly. Two important results are found. Firstly, both tests we use give similar p-values of the coefficients which indicate the significance of contagion. Secondly, for both tests, the contagion pattern in the equity and real estate markets are different. Our study has an implication to investors that they should regularly review their portfolio and be aware of contagion triggered by a crisis. This would help them reduce their loss and is useful in strategic property management.First Publish Online: 23 Sep 2013